Tourist Service Consumers in the Time of the Sharing Economy - Kowalska , Klaudyna (Studia Oeconomica Posnaniensia, 2018)
Research on the sharing economy is gaining popularity due to the development of initiatives and companies coordinating and supporting the exchange of services directly between consumers, such as Couchsurfing, Airbnb or BlaBlaCar. Along with their appearance, there have been changes in the behavior of consumers, including the roles they play in the tourism market. The purpose of the paper is to identify and analyze the role of tourism services consumer in the sharing economy. The research method used to achieve the aim of the study was an analysis of secondary sources. The first part of the paper presents an overview of the phenomenon. The second part presents the symptoms of the sharing economy in tourism and the problems related to its development. Further considerations refer to the changing role of the consumers of tourism services. The analysis helped to identify three roles: the recipient, the provider and the fully sharing consumer. Finally, conclusions and proposals for future research are presented.